A preparation method of a novel high-speed train insulator shed material

By preparing polyvinyl chloride matrix material and combining the synergistic effects of synergistic flame retardant and plasticizer, the problems of poor hydrophobic recovery, insufficient mechanical strength and low leakage resistance and traceability of high-speed train insulator material are solved, and high performance insulator material is achieved.

CN116622171BActive Publication Date: 2025-04-01SHANGHAI UNIV +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310663609.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-06
Publication Date
2025-04-01
Estimated Expiration
2043-06-06

AI Technical Summary

Technical Problem

When existing high-speed train insulator sub-umbrella skirt materials face wind and sand erosion, ultraviolet light exposure and high airflow impact force, there are problems such as poor hydrophobic recovery, insufficient mechanical strength and low leakage resistance and trace resistance.

Method used

By using polyvinyl chloride as the matrix material, the formulation of raw materials including dioctyl terephthalate, methyltin thiol, aluminum hydroxide, stearic acid, antioxidant, polytetrafluoroethylene, antimony trioxide and titanium dioxide is used to utilize the synergistic flame retardant effect of aluminum hydroxide and antimony trioxide, and the synergistic effect of plasticizer and polytetrafluoroethylene to improve the hydrophobicity and mechanical strength of the material.

Benefits of technology

It realizes excellent leakage resistance, long-lasting water repellency and high mechanical strength of insulator skirt materials, which is suitable for the composite insulator skirt materials of high-speed trains.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116622171B_ABST
    Figure CN116622171B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a novel high-speed train insulator shed material, comprising the following raw material components in parts by weight: 100 parts of polyvinyl chloride, 6-12 parts of dioctyl terephthalate, 3 parts of methyl tin mercaptide, 100-150 parts of aluminum hydroxide, 1 part of stearic acid, 1 part of 1010 antioxidant, 0-6 parts of polytetrafluoroethylene, 0-6 parts of antimony trioxide, 4 parts of titanium dioxide, and 4 parts of ACR401 additives. The method of the present invention utilizes the good insulation performance, aging resistance and mechanical properties of polyvinyl chloride itself, and utilizes the migration characteristics of the plasticizer, and under the synergistic effect of the polytetrafluoroethylene component, the surface hydrophobicity and hydrophobic recovery of the polyvinyl chloride material are improved, and the main electrical properties and hydrophobicity of the prepared polyvinyl chloride insulator meet the relevant technical conditions of the insulator, and the mechanical properties of the material are particularly outstanding, which is suitable as the shed material of the insulator of a high-speed train with a speed of more than 400 kilometers per hour.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrical composite materials, in particular to a method for preparing a novel high-speed train insulator shed material. Background Art

[0002] Insulators are special insulating components that can support conductors and prevent current from returning to the ground in overhead transmission lines. Roof insulators are the most critical components to ensure high-speed rail power supply and play an important role in high-speed rail contact networks. At present, silicone rubber composite insulators are mainly used on high-speed trains. They have the characteristics of small size, easy maintenance, light weight, easy installation, good pollution resistance and hydrophobicity. Patent CN101654558A discloses an insulator silicone rubber and a manufacturing method thereof. The raw materials include: raw rubber with a vinyl molar content of 1%, raw rubber with a vinyl molar content of 0.14%, fumed silica, dimethyl dimethoxy silane, aluminum hydroxide, vinyl trimethoxy silane, dimethyl silicone oil, and titanate coupling agent. The product has good insulation properties. At present, silicone rubber composite insulators are ranked first among the three major types of insulators, both in power grids and locomotives. However, with the further advancement of high-speed rail construction, higher requirements are put forward for composite insulators for high-speed trains. On the one hand, the high-speed rail transportation route spans across the north and south, requiring insulators to be able to resist erosion by wind and sand and maintain surface hydrophobicity to avoid flashover, leakage current tracking and other damage under the combined action of electric fields and dirt; on the other hand, there is the challenge brought by the speed increase of high-speed trains. The maximum speed of high-speed rail has exceeded 400km / h, and insulators need to have higher strength to cope with the greater impact of airflow to avoid vibration and cracking of insulators.

[0003] Since the mechanical properties of silicone rubber insulators themselves are poor and they are prone to cracking, the research and development of polyolefin insulators is very meaningful. Patent CN110423394A discloses a polyolefin insulator material with long-lasting hydrophobic properties. The raw materials include polyethylene, polypropylene, decabromodiphenylethane, antimony trioxide, antioxidants, silicone, light stabilizers and modified silicone oil compositions, which meet the basic performance requirements of insulators and give them longer-lasting hydrophobicity, hydrophobicity migration and anti-fouling properties. Patent CN109135002A discloses a polymer insulator material and a preparation method thereof. The raw materials include polyethylene, polypropylene, methyl silicone rubber and inorganic fillers. The prepared material has anti-fouling and self-cleaning functions. Patent CN105602248A discloses a polymer insulator material and a preparation method thereof. The raw materials include polyimide and zinc oxide powder, and the sample is prepared by a blending and compounding method. In general, the main materials used in the research and development of polyolefin insulators are polyethylene and polypropylene. The compatibility of silicone or silicone oil with polyolefin in the shed material of such insulators is poor, resulting in a small amount of addition, making the hydrophobic recovery not durable enough.

[0004] In addition, the inventors found in their research that the tracking failure mechanisms of polyvinyl chloride insulation shed materials and silicone rubber insulation shed materials are different: silicone rubber materials are easily decomposed and carbonized during the discharge process, and the generated free carbon will promote the development of arcs, and eventually form a conductive path connecting the upper and lower electrodes, resulting in sample test failure; while polyvinyl chloride shed materials undergo matrix decomposition at high temperatures, and the generated conjugated double bonds have good conductivity, which will promote the development of dry strip arcs, and eventually lead to local overheating and sample ignition failure. Therefore, this scheme starts with improving the flame retardancy of polyvinyl chloride shed materials to achieve the purpose of improving the tracking resistance performance. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a method for preparing a novel high-speed train insulator shed material. The insulator shed material prepared by the method has excellent tracking resistance, hydrophobicity and high mechanical strength.

[0006] The technical solution adopted by the present invention is as follows: a method for preparing a novel high-speed train insulator shed material, which includes the following raw material components in parts by weight: 100 parts of polyvinyl chloride, 6-12 parts of dioctyl terephthalate, 3 parts of methyl tin mercaptide, 100-150 parts of aluminum hydroxide, 1 part of stearic acid, 1 part of 1010 antioxidant, 0-6 parts of polytetrafluoroethylene, 0-6 parts of antimony trioxide, 4 parts of titanium dioxide, and 4 parts of ACR401 additive.

[0007] In the above formula, "0-6 parts of polytetrafluoroethylene" does not include the endpoint value of 0 part, and its minimum portion is greater than 0 part; further, "0-6 parts of antimony trioxide" does not include the endpoint value of 0 part, and its minimum portion is greater than 0 part. This formula improves the anti-leakage tracking performance of the polyvinyl chloride shed material through the synergistic flame retardant effect of aluminum hydroxide and antimony trioxide. The prepared samples do not produce open flames during the test process, and there are no obvious traces of electrical corrosion on the surface of the tested samples; the ultraviolet absorption performance of titanium dioxide is used to improve the ultraviolet resistance of polyvinyl chloride insulators; the plasticizer dioctyl terephthalate can not only improve the processability of the material, but also increase the amount of plasticizer added and cooperate with polytetrafluoroethylene, and use its mobility to make the material obtain lasting hydrophobicity and hydrophobic recovery; at the same time, the antioxidants and light stabilizers in the formula make the insulators have higher stability and longer service life. This formula system has achieved the development of high-performance polyvinyl chloride insulator shed material that integrates multiple properties such as electrical corrosion resistance, wear resistance, UV resistance, and pollution resistance, and is suitable for use as composite insulator shed material for high-speed EMU trains.

[0008] As a preferred technical solution of the present invention, the polyvinyl chloride grade is SG-5.

[0009] Preferably, the degree of polymerization of the polyvinyl chloride is 1180-1070.

[0010] Preferably, the grade of the methyltin mercaptan is SAK-MT9001.

[0011] Preferably, the methyl tin mercaptan has a tin content of 19.2% and a density of 1.180 g / cm3.

[0012] Preferably, the aluminum hydroxide has a particle size of 2-10 microns and is used in one specification or in a mixture of two specifications.

[0013] Preferably, the metal oxide content of the ACR401 additive is greater than 30%, and the apparent density is 0.2-0.7 g / cm3.

[0014] Preferably, the density of the stearic acid is 0.94 g / cm3 and the melting point is 70°C.

[0015] Preferably, the titanium dioxide is rutile, and the rutile content is 98%.

[0016] The specific preparation method of the above-mentioned new type of high-speed train insulator shed material is as follows: according to the above formula, polyvinyl chloride, methyl tin mercaptan, dioctyl terephthalate, aluminum hydroxide, ACR401, stearic acid, 1010 antioxidant and other raw materials are mixed evenly and put into an internal mixer for mixing and sampling at 170-180°C. After taking out, press it into a sheet on a double-roll open mill. Transfer it to a flat vulcanizer and hot press it at 170-180°C and 15 MPa for 10 minutes, and then cold press it at 15 MPa for 10 minutes; cut the cold-pressed sample to obtain the test specimen of the polyvinyl chloride shed material.

[0017] The beneficial effects of the present invention are as follows: the present invention uses polyvinyl chloride as a base material to prepare an insulator shed material with excellent comprehensive performance, specifically, the hydrophobicity and hydrophobic recovery of the shed material are improved through the synergistic effect of a plasticizer and polytetrafluoroethylene, and the tracking resistance of the material is improved through the synergistic flame retardancy of aluminum hydroxide and antimony trioxide; the shed material prepared by this scheme has excellent tracking resistance and hydrophobicity at the same time, and the mechanical strength of the polyvinyl chloride shed material is much higher than that of the silicone rubber shed material. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying creative labor, other drawings obtained based on these drawings still belong to the scope of the present invention.

[0019] Figure 1These are digital photos of samples after tracking: Comparative Example 3 (a), Comparative Example 4 (b), Comparative Example 5 (c);

[0020] Figure 2 Pictures of samples after tracking test: Example 1 (left), Comparative Example 6 (right). DETAILED DESCRIPTION

[0021] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.

[0022] Example 1

[0023] A polyvinyl chloride insulator shed material, whose formula includes the following raw material components in parts by weight: 100 parts of polyvinyl chloride, 10 parts of dioctyl terephthalate, 3 parts of methyl tin mercaptide, 150 parts of aluminum hydroxide, 1 part of stearic acid, 1 part of 1010 antioxidant, 4 parts of titanium dioxide, 6 parts of polytetrafluoroethylene, 6 parts of antimony trioxide, and 4 parts of ACR401 additive.

[0024] The test sample preparation method was as described above.

[0025] Example 2

[0026] A polyvinyl chloride insulator shed material, whose formula includes the following raw material components in parts by weight: 100 parts of polyvinyl chloride, 8 parts of dioctyl terephthalate, 3 parts of methyl tin mercaptide, 150 parts of aluminum hydroxide, 1 part of stearic acid, 1 part of 1010 antioxidant, 4 parts of titanium dioxide, 6 parts of polytetrafluoroethylene, 6 parts of antimony trioxide, and 4 parts of ACR401 additive.

[0027] The test sample preparation method was as described above.

[0028] Example 3

[0029] A polyvinyl chloride insulator shed material, the formula of which comprises the following raw material components in parts by weight: 100 parts of polyvinyl chloride, 6 parts of dioctyl terephthalate, 3 parts of methyl tin mercaptide, 150 parts of aluminum hydroxide, 1 part of stearic acid, 1 part of 1010 antioxidant, 4 parts of titanium dioxide, 6 parts of polytetrafluoroethylene, 6 parts of antimony trioxide, and 4 parts of ACR401 additive.

[0030] The test sample preparation method was as described above.

[0031] Example 4

[0032] A polyvinyl chloride insulator shed material, the formula of which comprises the following raw material components in parts by weight: 100 parts of polyvinyl chloride, 10 parts of dioctyl terephthalate, 3 parts of methyl tin mercaptide, 150 parts of aluminum hydroxide, 1 part of stearic acid, 1 part of 1010 antioxidant, 4 parts of titanium dioxide, 3 parts of polytetrafluoroethylene, 6 parts of antimony trioxide and 4 parts of ACR401 additive.

[0033] The test sample preparation method was as described above.

[0034] Example 5

[0035] A polyvinyl chloride insulator shed material, the formula of which comprises the following raw material components in parts by weight: 100 parts of polyvinyl chloride, 10 parts of dioctyl terephthalate, 3 parts of methyl tin mercaptide, 150 parts of aluminum hydroxide, 1 part of stearic acid, 1 part of 1010 antioxidant, 4 parts of titanium dioxide, 6 parts of antimony trioxide, and 4 parts of ACR401 additive.

[0036] The test sample preparation method was as described above.

[0037] Comparative Example 1

[0038] A polyvinyl chloride insulator shed material, the formula of which comprises the following raw material components in parts by weight: 100 parts of polyvinyl chloride, 12 parts of dioctyl terephthalate, 3 parts of methyl tin mercaptide, 150 parts of aluminum hydroxide, 1 part of stearic acid, 1 part of 1010 antioxidant, 4 parts of titanium dioxide, 6 parts of polytetrafluoroethylene, 6 parts of antimony trioxide, and 4 parts of ACR401 additive.

[0039] The test sample preparation method was as described above.

[0040] Comparative Example 2

[0041] A polyvinyl chloride insulator shed material, the formula of which comprises the following raw material components in parts by weight: 100 parts of polyvinyl chloride, 10 parts of dioctyl terephthalate, 3 parts of methyl tin mercaptide, 100 parts of aluminum hydroxide, 1 part of stearic acid, 1 part of 1010 antioxidant, 4 parts of titanium dioxide, 6 parts of polytetrafluoroethylene, 6 parts of antimony trioxide, and 4 parts of ACR401 additive.

[0042] The test sample preparation method was as described above.

[0043] Comparative Example 3

[0044] A polyvinyl chloride insulator shed material, the formula of which comprises the following raw material components in parts by weight: 100 parts of polyvinyl chloride, 10 parts of dioctyl terephthalate, 3 parts of methyl tin mercaptide, 50 parts of aluminum hydroxide, 1 part of stearic acid, 1 part of 1010 antioxidant, 4 parts of titanium dioxide, 6 parts of polytetrafluoroethylene, and 4 parts of ACR401 additive.

[0045] The test sample preparation method was as described above.

[0046] Comparative Example 4

[0047] A polyvinyl chloride insulator shed material, the formula of which comprises the following raw material components in parts by weight: 100 parts of polyvinyl chloride, 10 parts of dioctyl terephthalate, 3 parts of methyl tin mercaptide, 50 parts of aluminum hydroxide, 1 part of stearic acid, 1 part of 1010 antioxidant, 4 parts of titanium dioxide, 6 parts of polytetrafluoroethylene, 3 parts of antimony trioxide, and 4 parts of ACR401 additive.

[0048] The test sample preparation method was as described above.

[0049] Comparative Example 5

[0050] A polyvinyl chloride insulator shed material, the formula of which comprises the following raw material components in parts by weight: 100 parts of polyvinyl chloride, 10 parts of dioctyl terephthalate, 3 parts of methyl tin mercaptide, 50 parts of aluminum hydroxide, 1 part of stearic acid, 1 part of 1010 antioxidant, 4 parts of titanium dioxide, 6 parts of polytetrafluoroethylene, 6 parts of antimony trioxide, and 4 parts of ACR401 additive.

[0051] Comparative Example 6

[0052] A polyvinyl chloride insulator shed material, the formula of which comprises the following raw material components in parts by weight: 100 parts of polyvinyl chloride, 10 parts of dioctyl terephthalate, 3 parts of methyl tin mercaptide, 150 parts of aluminum hydroxide, 1 part of stearic acid, 1 part of 1010 antioxidant, 4 parts of titanium dioxide, 6 parts of polytetrafluoroethylene, and 4 parts of ACR401 additive.

[0053] The specific preparation method of the above formula is as follows: according to the formula, polyvinyl chloride, methyl tin mercaptan, dioctyl terephthalate, aluminum hydroxide, ACR401, stearic acid, 1010 antioxidant and other raw materials are mixed evenly and put into an internal mixer for mixing and sampling at about 175°C. After taking out, it is pressed into a sheet on a double-roll open mill. It is transferred to a flat vulcanizer for hot pressing at 170°C and 15 MPa for 10 minutes, and then cold pressing at 15 MPa for 10 minutes; the cold pressed sample is cut to obtain the test specimen of the polyvinyl chloride shed material.

[0054] Performance Testing

[0055] The performance of the polyvinyl chloride shed materials provided in the above embodiments and comparative examples was tested, and the test items and standards were as follows:

[0056] Tracking performance: GB / T 6553, GB / T34937

[0057] Hydrophobicity test: DL / T 1474

[0058] Impact strength test: GB / T 2567

[0059] Bending strength test: GB / T 2567

[0060] Shore hardness: GB / T 2411

[0061] Breakdown strength test: GB / T 1408.1

[0062] Examples 1, 2, 3, 4, 5 and Comparative Examples 1 and 6 can all pass the 360-min tracking test. The test results of other comparative examples are shown in the following table (the time for passing the tracking test is 360 min):

[0063]

[0064] Also refer to Figure 1-2 , it was found that the amount of antimony trioxide added had a significant effect on the tracking performance. When the amount of antimony trioxide added increased, the tracking test time of the sample was prolonged, and the corrosion marks after the test failure were fewer. The amount of flame retardant ATH (aluminum hydroxide) added was the key to the tracking performance passing, and the synergistic effect with antimony trioxide reduced the corrosion marks on the sample surface; Figure 2 Example 1 and Comparative Example 6 compare the surface electrolytic corrosion marks under the same aluminum hydroxide content and tolerance time, indicating that the increase of antimony trioxide reduces the surface electrolytic corrosion marks, proving that the synergistic flame retardancy of antimony trioxide and aluminum hydroxide can effectively reduce the electrolytic corrosion marks on the sample surface.

[0065] The impact strength, bending strength and Shore D hardness test results of the material are shown in Table 2 below:

[0066]

[0067] As shown in Table 2, when the amount of aluminum hydroxide added increases, the impact strength of the material shows a downward trend, and the flexural strength and hardness show an upward trend; with the gradual increase in the amount of plasticizer (dioctyl terephthalate) added, the hardness of the sample shows a trend of first increasing and then decreasing. When the amount of plasticizer added is greater than 10phr, the hardness, flexural strength and impact strength of the sample begin to decrease.

[0068] In this scheme, the plasticizer (dioctyl terephthalate) as a bifunctional component can not only improve the plasticity and processability of the material, but also restore the surface hydrophobicity through migration; the migration of plasticizer molecules is directly related to its addition amount, and its hydrophobic recovery can be affected by changing the addition amount; the effects of plasticizer (dioctyl terephthalate) and polytetrafluoroethylene on the hydrophobicity classification and contact angle test of the material are shown in Table 3 below:

[0069]

[0070] Plasticizers have a significant effect on improving the hydrophobic recovery of materials. Specifically, the greater the amount of plasticizer added, the greater the contact angle of the sample after the weakening test and the recovery test, and the higher the hydrophobicity grade, but the effect of plasticizers on the initial contact angle is small. Polytetrafluoroethylene has a significant effect on improving the initial contact angle of the material. The contact angle of the material increases first and then decreases with the increase in the amount of polytetrafluoroethylene added. The synergy between polytetrafluoroethylene and plasticizers is reflected in: when the plasticizer content is the same, the greater the amount of polytetrafluoroethylene added, the greater the recovery contact angle of the sample, and the better the hydrophobic recovery, indicating that polytetrafluoroethylene can promote the migration of plasticizers to a certain extent (Examples 1, 4, 5). It should be noted that within the range of the material ratio and process parameters recorded in the present invention, specific values ​​can be selected at will, and the resulting materials can achieve the technical effects recorded in the present invention. Therefore, the present invention will no longer list them one by one.

[0071] The above description is only a preferred embodiment of the present invention and does not limit the technical scope of the present invention. Therefore, any technical features that are the same or similar to those of the above-mentioned embodiments of the present invention are within the protection scope of the present invention.

Claims

1. A high-speed train insulator shed material, characterized in that The invention comprises the following raw material components in parts by weight: 100 parts of polyvinyl chloride, 6-10 parts of dioctyl terephthalate, 3 parts of methyl tin mercaptide, 150 parts of aluminum hydroxide, 1 part of stearic acid, 1 part of 1010 antioxidant, 0-6 parts of polytetrafluoroethylene, 0-6 parts of antimony trioxide, 4 parts of titanium dioxide and 4 parts of ACR401 additive; the parts of the above polytetrafluoroethylene and antimony trioxide do not include the endpoint value of 0 part.

2. The high-speed train insulator shed material according to claim 1, characterized in that: The degree of polymerization of the polyvinyl chloride is 1180-1070.

3. The high-speed train insulator shed material according to claim 1, characterized in that: The tin content of the methyl tin mercaptan is 19.2%, and the density is 1.180 g / cm3.

4. The high-speed train insulator shed material according to claim 1, characterized in that: The aluminum hydroxide has a particle size of 2-10 microns and is used in a single specification or in a combination of multiple specifications.

5. The high-speed train insulator shed material according to claim 1, characterized in that The density of stearic acid is 0.94 g / cm3 and the melting point is 70°C.

6. The high-speed train insulator shed material according to claim 1, characterized in that: The titanium dioxide is rutile, and the rutile content is 98%.

7. The method for preparing a high-speed train insulator shed material according to claim 1, characterized in that: The specific preparation steps are as follows: the raw materials are mixed evenly according to the formula and then put into an internal mixer, mixed and sampled at 170-180°C, then pressed into sheets on an open mixer, and then transferred to a flat vulcanizer for hot pressing at 170-180°C and 15 MPa for 8-12 min, and then cold pressing at 15 MPa for 8-12 min to obtain the umbrella skirt material.

Citation Information

Patent Citations

  • Insulator silicon rubber and method for preparing same

    CN101654558A

  • Polymer insulator material and preparation method thereof

    CN105602248A

  • Polymer insulator material and preparation method thereof

    CN109135002A

  • Polyolefin insulator material with long-lasting hydrophobic properties

    CN110423394A

  • Special material for polychloroethylene insulating electrical casing pipe

    CN101177512A